Validasi Metode Analisis Cemaran DNA Babi pada Bakso Sapi Menggunakan Primer Mitokondria D-Loop22 dengan Metode Polymerase Chain Reaction (PCR): Analysis Method Validation of Pig DNA Contamination in Cow Meatballs Using Mitochondrial Primer D-Loop22 by Polymerase Chain Reaction (PCR) Method - Wahyuni, Sri; Maryam, Siti; Aminah, Aminah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
The frequency of non-halal ingredient mixing, such as porkin on the food processed products of meatballs, has become an issue to the public, especially for moslems. Therefore, a reliable and valid method with high sensitivity is needed to specifically detect the pig contamination. This research aims to obtain a valid and reliable method by proposing polymerase chain reaction (PCR) using mitochondrial D-Loop22 primer as a method in handing halal food authentication. The sample consisted of beef as a negative control, pork and pork meatballs as a positivecontrol, and five samples of meat balls found in Makassar for halal inspection.The method validation assay was conducted by testing the primary specificity on the fresh tissue (beef and pork) and testing the sensitivity by making a series of pig DNA dilution (1:10; 1:102; 1:103; 1:104) and the variations of contaminated pig:cow (%b/b) : 0.05% , 0.1%, 1%, and 5%. The result of PCR amplification on agarose gel electrophoresis of 0.8% showed that method was able to detect the pig DNA contamination specifically in pigs and not amplify other DNA, and could still be detected up to pig contamination specifically in pigs and not amplify the other DNAs and could still be detected up to pig contamination of 0.05% and on DNA dilution of 1:103. Meanwhile, on the five samples analyzed, there were not found pig DNA contamination characterized by no formed amplification bands.